In vitro immunomodulation activity of protein hydrolysate from spirulina (Arthrospira platensis): the ingredient of future foods - Htoo, Nang Yee Mon; Kraseasintra, Oranit; Buncharoen, Wararut; Kaewkod, Thida; Pekkoh, Jeeraporn; Tragoolpua, Yingmanee; Khoo, Kuan Shiong; Chaipoot, Supakit; Srinuanpan, Sirasit; Pumas, Chayakorn (Frontiers in Marine Science, 2024)
Microalgae, especially spirulina, have been globally used as a food supplement due to their rich protein content, safety for human consumption, and provision of enhanced immunomodulatory capabilities. There are, however, few reports that have investigated the immunomodulatory properties of spirulina protein hydrolysate. Consequently, this study aims to optimize the best extraction techniques for spirulina protein hydrolysate and characterize its antioxidant activities and immunomodulation properties in vitro. The results indicated that protein hydrolysate with Flavourzyme and alkaline extraction after ultrasonication and pre-enzymatic assistant with cellulase exhibited superior antioxidant properties compared to other methods. Additionally, all the protein extracts demonstrated a dose-dependent inhibition of nitric oxide production without significantly impacting cell viability. Furthermore, in vitro immunomodulatory properties were evaluated using Candida albicans (DMST 5815) as the test pathogen, with phagocytic activity and index measurements conducted. Notably, the results correlated with the previous assessments, wherein the protein hydrolysate with Flavourzyme displayed the highest phagocytic percentage, measuring 52.3% at a concentration of 10 mg/mL. These findings suggest that enzymatically derived protein hydrolysates from spirulina could serve as a potential source for enhancing immunostimulant activity. Thus, they hold promise as natural bioactive ingredients for therapeutic purposes and the development of functional foods.